Where are the development actors in protracted crises? Refugee livelihood and food security outcomes in South Sudan demonstrate the potential for fragile settings. (December 2021) - Vallet, Maryada E.; Frankenberger, Timothy R.; Presnall, Carrie; Otieno, Lilian; Fu, Christine; Lee, Ellen
Highlights: Refugees in protracted settings are able to save, build assets, diversify livelihoods Positive benefits are realized when integrating savings and livelihood interventions Long-term investment in the enabling environment is needed for sustainable impact Development actors have roles in humanitarian contexts supporting the triple nexus VSLA build financial and social capital for livelihoods in fragile refugee areas Abstract: This paper presents findings from a mixed-methods performance evaluation of United Nations High Commissioner for Refugees (UNHCR) livelihood programming in South Sudan, implemented between 2016 and 2018 and aimed at promoting refugee self-reliance in a fragile context characterized by protracted conflict and displacement. Utilizing a quantitative survey with a randomized sample of refugee participants (n = 406) in Maban and Unity refugee hosting areas, as well as qualitative interviews of 188 participants and other key informants, the study assessed the effect of livelihood interventions, as compared to the same support plus access to informal financial services through Village Saving and Loan Associations (VSLAs), on reported outcomes. The study finds that despite the challenges posed by the fragile setting, UNHCR-funded programming likely contributed to increased income, employment, savings, and assets for participants (though study design does not allow conclusive impact attribution). Further, statistically significant differences were found in livelihood and food security outcomes of refugees participating in combined livelihood training and VSLAs versus only training. Moreover, UNHCR activities reduced conflict with host communities. Whereas scalable impact and sustainability are limited by weak infrastructure, security, and enabling systems, this paper provides evidence of development impacts supporting inclusive economic development and peacebuilding in remote fragile areas, thus enacting ideals of the Humanitarian-Development-Peace Triple Nexus and the Global Compact on Refugees. We argue for the need for additional multi-stakeholder engagement from development, government, and private sector actors in enhancing refugees' economic inclusion in this difficult context.